Pembuatan Larvasida Daun Jeruk Limau Dan Kelambu Air Untuk Pencegahan Kasus Demam Berdarah Karang Joang: Making Larvicides from Lime Leaves and Water Mosquito Nets to Prevent Cases of Dengue Fever in Karang Joang - Lusi Ernawati; Dian Rahmawati; Asful Hariyadi; Riza Alviany (Future Science, 2022)
The health office in Balikpapan is still tracking the number of dengue cases, which has reached at least 90 cases, until the third week of March 2022. During this outbreak, almost everyone is focused on avoiding and treating Covid-19 infections. Dengue fever is an illness to which you should pay close attention. In particular, because dengue fever remains a dangerous sickness in Indonesia. A range of approaches, including the use of larvicides, have been used to prevent and control dengue hemorrhagic fever (DBD). It is only that the mosquito that spreads Dengue Hemorrhagic Fever (DBD) has become susceptible to chemical larvicides, which are widely used by the general public. The purpose of this community service project is to teach people how to produce environmentally friendly natural larvicides from lime leaves. Community socialization, training in how to create larvicide, and knowledge evaluation are all part of the implementation phase. The memorial service will be place in Karang Joang North Balikpapan. Through lectures question and answer sessions, the community gets involved in the implementation process. Training and the use of health protocols are used directly in the manufacturing of larvicides. Water nets were built in several water reservoirs owned by homeowners, as well as similar programs involving of the monitoring and evaluation to provide the instruction and training on natural larvicide technology.